Exile from the Grasslands : Tibetan Herders and Chinese Development Projects - Ptáčková, Jarmila; Ptáčková, Jarmila (Book collections on Project MUSE., 2020)
"At the start of the new millennium, the Chinese government launched an ambitious new development program with far-reaching economic, environmental, and cultural effects in remote areas inhabited mainly by indigenous ethnic groups. The Great Opening of the West program diverts pastoral Tibetans to urban residence and urban livelihoods, resulting in a massive shift in social and economic patterns. Based on fieldwork that has been ongoing since 2007, this ethnography documents the transformation of Tibetan pastoral society in Qinghai Province under Chinese development efforts. It describes sedentarization and relocation policy agendas, viewpoints of both the affected pastoral population and officials charged with implementing policy, and case studies of pastoralists' response to sedentarization and other grassland management policies."